Ethics, economics and the human subsistence through trade - Maia Batista, Álvaro (Argumentos - Revista do Departamento de Ciências Sociais da Unimontes, 2021)
This work reflects on the relation between ethics, economics and the human subsistence, which in urban societies occurs through trade. The interest is to understand how the economic life of westernized societies was created and to investigate a possible alternative. In order to do so, it starts with a critical analysis of the significance that trade assumes in these societies and continues with the review of some ethical conceptions developed by economists. In the end, it presents a radical ethical proposal accompanied by the revision of the concept of revolution, both elaborated in the wake of Emmanuel Levinas’ thinking.